The Roles of Exosomal microRNAs in Diffuse Large B-Cell Lymphoma: Diagnosis, Prognosis, Clinical Application, and Biomolecular Mechanisms - Yazdanparast, Somayeh; Huang, Zoufang; Keramat, Shayan; Izadirad, Mehrdad; Li, Yi-Dong; Bo, Letao; Gharehbaghian, Ahmad; Chen, Zhe-Sheng (Frontiers in Oncology, 2022)
Background Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous neoplasm and is characterized as the most common subtype of non-Hodgkin lymphoma (NHL). Despite 60–70% of all patients being cured with R-CHOP therapeutic regimen (Cyclophosphamide, doxorubicin, vincristine, and prednisone, combined with rituximab), remaining patients display aggressive disease. Therefore, there is an urgent need to develop novel diagnostic, prognostic, and predictive biomarkers. Recently, exosomal miRNAs have been approved as novel biomarkers in DLBCL due to their potential involvement in lymphomagenesis. Material and Methods We conducted an investigation on the potential role of exosomal miRNAs as diagnostic, prognostic, and predictive biomarkers in DLBCL in the PubMed, Scopus, and Web of Science search engines. We searched by using a combination of keywords, such as diffuse large B-cell lymphoma, DLBCL, miRNA, microRNA, miR, exosome, exosomes, exosomal, extracellular vesicles, EVs, and secretome. Then, search results were narrowed based on specific inclusion and exclusion criteria. Results Twelve articles were eligible for our systematic reviews. Among them, nine discussed diagnostic biomarkers, three considered prognostic significance, four evaluated therapeutic efficacy, two studies were conducted in vitro, and three assessed molecular pathways associated with these exosomal miRNAs in DLBCL. Discussion According to our systematic review, exosomal miRNAs are not only useful for diagnosis and prognosis in DLBCL but are also promising therapeutic tools and predictors of response to therapy. Although promising results so far, more research is required to develop innovative biomarkers.